Pengaruh Infrastruktur Terhadap Pertumbuhan Ekonomi Di Sumatera Selatan - Septi Indah Sari; Cut putri Mellita Sari (LPPM UNIMAL, 2021)
This study examines the effect of road infrastructure, electricity infrastructure, and PDAM infrastructure on economic growth in South Sumatra using time-series data from 2005 to 2018. The analytical method used in this research is Ordinary Least Square (OLS). The partial test results show that road infrastructure, electricity infrastructure, and PDAM infrastructure do not affect economic growth. Meanwhile, road infrastructure, electricity infrastructure, and PDAM infrastructure have a significant effect on economic growth simultaneously. The coefficient of determination (R²) is 0.737163, which means that the effect of road infrastructure, electricity infrastructure, and water infrastructure on economic growth in South Sumatra province is 0.737163 or 73.71%, and the remaining 26.29% is influenced by variables outside of this study. The correlation coefficient in this study is 0.8585 or 85.85%. So the level of relationship that Road Infrastructure, Electricity Infrastructure, and Water Infrastructure have on Economic Growth are very strongly linked.Keywords:Economic Growth, road infrastructure, electricity infrastructure, and PDAM infrastructure.